Использование щелевых резонаторов для проектирования усилителя мощности с манипуляцией гармоник - Rassokhina, Yu. V.; Krizhanovski, V. G.; Kovalenko, V. A.; Colantonio, P.; Giofre, R. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
The authors proposed and experimentally verified the power amplifier circuit of inverse class F (F–1) based on GaN transistor NPTB00004, operating at 1,7 GHz. The novelty of this scheme is the application of a three-layer structure based on slot rectangular shaped resonators in the ground plane of the microstrip transmission line as a filter of higher harmonics. To control the levels of the second and third harmonics in the output signal spectrum and simultaneously to match the 50 ohm load at the operating frequency of the amplifier, a planar periodic structure is used, consisting of two slot resonators of different lengths. Power added efficiency for experimental model of the amplifier is 60% at an output power of 3.9 W and a gain factor of 13 dB.